2002
DOI: 10.1021/ic010710l
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Image Generation in a Cyanogel System Synthesized from Tetrachloropalladate(II) and the Trimetallic Mixed-Valence Complex [(NC)5FeII−CN−PtIV(NH3)4−NC−FeII(CN)5]4-:  Consideration of Photochemical and Dark Mechanistic Pathways of Prussian Blue Formation

Abstract: The cyanogel system involving PdCl(4)(2-) and the mixed-valence complex [(NC)(5)Fe(II)-CN-Pt(IV)(NH(3))(4)-NC-Fe(II)(CN)(5)](4-) is reported. The system has been characterized by UV-vis absorption, diffuse reflectance infrared, and resonance Raman spectroscopies. Gelation occurs through coordination of Pd(II) to the nitrogen atom of terminal cyanide ligands in the mixed-valence complex. Irradiation into the Fe(II) --> Pt(IV) intervalent electron transfer (IT) band of [(NC)(5)Fe(II)-CN-Pt(IV)(NH(3))(4)-NC-Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…and the nitrogen atom from the cyano ligand in transition-metal cyanometalates (K 2 Ni­(CN) 4 , K 3 Co­(CN) 6 , K 3 Fe­(CN) 6 , etc.) in aqueous solutions (Figure A). According to the structural formula of the cyanogel, 2D planar units exist in the CoCl 2 /K 3 Co­(CN) 6 cyanogel (Figure B). Due to the solid nature of the CoCl 2 /K 3 Co­(CN) 6 cyanogel, the new generated crystal nuclei preferentially assemble at the solid–liquid interface rather than in solution after adding NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…and the nitrogen atom from the cyano ligand in transition-metal cyanometalates (K 2 Ni­(CN) 4 , K 3 Co­(CN) 6 , K 3 Fe­(CN) 6 , etc.) in aqueous solutions (Figure A). According to the structural formula of the cyanogel, 2D planar units exist in the CoCl 2 /K 3 Co­(CN) 6 cyanogel (Figure B). Due to the solid nature of the CoCl 2 /K 3 Co­(CN) 6 cyanogel, the new generated crystal nuclei preferentially assemble at the solid–liquid interface rather than in solution after adding NaBH 4 .…”
Section: Resultsmentioning
confidence: 99%
“…108,109 This technology has been further developed by the same group using a rigid sol-gel-generated matrix incorporating the aforementioned cyanometalate complex. 110 In situ photogeneration of Prussian blue has been demonstrated earlier in an Fe(CN) 6 3-/4--loaded chemically modified electrode containing a quaternized polyvinylpyridine layer. 111 6.3.…”
Section: Applications Of Mhcf Compoundsmentioning
confidence: 85%
“…Trimetallic mixed-valence anions, [(NC) 5 Fe II −CN−Pt IV (NH 3 ) 4 −NC−Fe II −(CN) 5 ] 4- and their photoproducts, when confined in a rigid matrix, produce images on irradiation. , It has been shown that Prussian blue is formed in situ under such conditions. , The ability to generate images accrues from differences in the spectra of Prussian blue and the above anion and the resulting optical contrast between the irradiated and “dark” portions of the film. Image generation with a scale on the order of 1 μm was demonstrated by irradiating through a mask. , This technology has been further developed by the same group using a rigid sol−gel-generated matrix incorporating the aforementioned cyanometalate complex . In situ photogeneration of Prussian blue has been demonstrated earlier in an Fe(CN) 6 3-/4- -loaded chemically modified electrode containing a quaternized polyvinylpyridine layer …”
Section: Applications Of Mhcf Compoundsmentioning
confidence: 99%
“…In other words, the extinction coefficients report on the effective concentration of {Co III −NC−Fe II } chromophores within the complex. It is interesting to note that the existence of up to six units should be, in principle, possible for these type of compounds, which would make them attractive targets for electrochromic applications. , …”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the existence of up to six units should be, in principle, possible for these type of compounds, which would make them attractive targets for electrochromic applications. 38,39 Table 3 collects the differences observed for the energy and intensity of the MMCT band for the trans-[{Co III L 14 (µ-NC)} 2 Fe II (CN) 4 ] 2+ species in different solvents and at low concentrations to avoid undesirable ionic-strength effects. The trend of the MMCT energy is in excellent agreement with the predicted shift (Figure S1a) because of changes in the static and optical dielectric constants of the solvent for a MMCT band.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%